The Treatment of Agitated and Aggressive Behaviors in Vascular Dementia Based on the Theory of “Heat Coagulating Blood Vessels” - Liu, Cancan; Hu, Jingqing (Journal of Contemporary Medical Practice, 2026)
The theory of “heat accumulation in blood vessels” was proposed by Researcher Hu Jingqing through a comprehensive review of traditional Chinese medical literature, clinical experience, and therapeutic optimization, combined with theoretical exploration. This theory builds upon the traditional pathogenic mechanisms of phlegm-heat, blood stasis-heat, and the mutual entanglement of phlegm and blood stasis leading to heat, and takes “heat accumulation” as the key point to summarize the common pathogenic mechanisms of various diseases centered on vascular lesions (such as cardiovascular and cerebrovascular conditions) or those where the vasculature is affected in their pathological processes. Researcher Hu Jingqing pointed out that the pathogenesis of vascular dementia mainly involves three aspects: “deficiency”, “phlegm”, and “blood stasis”. However, the agitated and aggressive behaviors are secondary mental disorders on the basis of vascular dementia, which cannot be fully explained by the three aspects of “deficiency”, “phlegm”, and “blood stasis”. Based on the theory of “heat accumulation in blood vessels”, the pathogenic evolution of agitated and aggressive behaviors in vascular dementia can be summarized as follows: the long-term entanglement of “deficiency”, “phlegm”, and “blood stasis” eventually leads to the generation of heat and fire, which further breeds toxins and causes disorders, damaging the blood vessels and forming a vicious cycle of accumulated heat → toxin formation → symptom formation → vessel damage.